Cold Atmospheric Plasma Triggers Apoptosis via the Unfolded Protein Response in Melanoma Cells - Zimmermann, Tom; Stäbler, Sebastian; Taudte, R. Verena; Ünüvar, Sumeyya; Groesch, Sabine; Arndt, Stephanie; Karrer, Sigrid; Fromm, Martin; Boßerhoff, Anja Katrin (Cancers, 2023)
Cold atmospheric plasma (CAP) describes a partially ionized gas carrying large amounts of reactive oxygen (ROS) and nitrogen species (RNS). Numerous studies reported strong antitumor activity of CAP, thus rendering it a promising approach for tumor therapy. Although several cellular mechanisms of its cytotoxicity were identified in recent years, the exact molecular effects and contributing signaling pathways are yet to be discovered. We discovered a strong activation of unfolded protein response (UPR) after CAP treatment with increased C/EBP homologous protein (CHOP) expression, which was mainly caused by protein misfolding and calcium loss in the endoplasmic reticulum. In addition, both ceramide level and ceramide metabolism were reduced after CAP treatment, which was then linked to the UPR activation. Pharmacological inhibition of ceramide metabolism resulted in sensitization of melanoma cells for CAP both in vitro and ex vivo. This study identified a novel mechanism of CAP-induced apoptosis in melanoma cells and thereby contributes to its potential application in tumor therapy.
CRIS-Team Scopus Importer:2023-03-10
Keywords: apoptosis; ceramide; cold atmospheric plasma; melanoma; unfolded protein response